Case study on the therapeutic approach to stress fractures - Breha Alexandru Mihai; Pavel Răzvan Cristian; Morari George (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement)
Sports pathology is in continuous progress, stress fractures are present in a high percentage among amateur athletes as well as among professionals. In the first stage of recovery, the exercises were mainly used in the supine position, the aim was to reduce the pressure at the lower level, therefore walking with a crutch was chosen. Central to the recovery plan was the exercises used in the pool. These were integrated in the second stage, more precisely in the 5th recovery week, because it allowed unloading the weight in the water and facilitated mechanical work with resistance on all the targeted muscle groups. The exercises specific to the practiced sport were used in the last stage to integrate the athlete into the complexity of the game and reduce the occurrence of recurrence at the tibial level. The approach from the medical point of view is based on the multidisciplinary team that is composed of a doctor, physiotherapist and nutritionist to provide a successful medical procedure.